2003
DOI: 10.1016/s0168-9002(02)01798-9
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the electromagnetic character of soft dipole modes solely based on quasicontinuous γ spectroscopy

Abstract: We show that the combined analysis of the quasicontinuous γ spectra from the ( 3 He,α) and the (n th , 2γ) reactions gives the possibility to measure the electromagnetic character of soft dipole resonances. Two-step γ-cascade spectra have been calculated, using level densities and radiative strength functions from the ( 3 He,αγ) reaction. The calculations show that the intensity of the twostep cascades depends on the electromagnetic character of the soft dipole resonance under study. The difference reaches 40-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…It has been shown that TSC intensities from ordered spectra can be used to investigate the soft RSF [12,13]. The TSC technique for thermal neutron capture has been described in [14].…”
mentioning
confidence: 99%
“…It has been shown that TSC intensities from ordered spectra can be used to investigate the soft RSF [12,13]. The TSC technique for thermal neutron capture has been described in [14].…”
mentioning
confidence: 99%